Effects of Exercise on Depression, Anxiety, Cognitive Control, Craving, Physical Fitness and Quality of Life in Methamphetamine-Dependent Patients - Junhao Huang; Yuqing Zheng; Dongdong Gao; Min Hu; Tifei Yuan; Tifei Yuan (Frontiers in Psychiatry, 2020)
Methamphetamine (MA) abuse results in a variety of harmful changes in mood states and cognitive function, together with declined physical health and quality of life. Recent studies highlighted the therapeutic potential of physical exercise on MA addiction. Physical exercise improves emotional state and general health conditions, enhances cognitive function, reduces relapse rate, and facilitates abstinence, thereby improves the overall quality of life of the drug users. This review summarizes the present situation of physical exercise on MA-dependent patients with both animal and clinical population results.